2021
DOI: 10.1037/xan0000299
|View full text |Cite
|
Sign up to set email alerts
|

Extending a misallocation model to children’s choice behavior.

Abstract: Nonhuman animal models show that reinforcers control behavior through what they signal about the likelihood of future events, but such control is generally imperfect. Imperfect control by the relation between past and likely future events may result from imperfect detection of those events as they occur, which result in imperfect detection of the relation between events. Such an approach would suggest the involvement of more complex psychological processes like memory in simple operant learning. We extended a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These studies generally occur in laboratories with animals. Mathematical models have shown that animal choice behavior is orderly (Baum, 1974;Davison & Jenkins, 1985) and conforms to the same general rules as human choice (Cowie et al, 2021;Podlesnik et al, 2022). The relationship between choice and environment can be described by linear regression by analyzing choice data as logarithmic ratios of the subject responses and ratios of the reward obtained (Davison & McCarthy, 1988).…”
Section: Experimental Analysis Of Behavior and Behavior Changementioning
confidence: 99%
“…These studies generally occur in laboratories with animals. Mathematical models have shown that animal choice behavior is orderly (Baum, 1974;Davison & Jenkins, 1985) and conforms to the same general rules as human choice (Cowie et al, 2021;Podlesnik et al, 2022). The relationship between choice and environment can be described by linear regression by analyzing choice data as logarithmic ratios of the subject responses and ratios of the reward obtained (Davison & McCarthy, 1988).…”
Section: Experimental Analysis Of Behavior and Behavior Changementioning
confidence: 99%
“…The next two papers study cognitive processes involved in tasks thought to engage sequence learning processes. The paper by Cowie et al (2021) focuses on a misallocation model of two-step sequence learning in young children and explores from a behavior-analytic viewpoint the implications of assuming that reinforcement might be misattributed to a misremembered response at the beginning of the behavioral sequence. Earlier studies by these authors have established some generality across other animal species of the operation of their misallocation rule.…”
mentioning
confidence: 99%